2017
DOI: 10.1653/024.100.0315
|View full text |Cite
|
Sign up to set email alerts
|

Brown Marmorated Stink Bug (Hemiptera: Pentatomidae) Attraction to Various Light Stimuli

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similarly, nymphs and adults of the Miridae Lygus hesperus Knight were attracted to the green color [ 3 ], and adults of the Pentatomidae Halyomorpha halys were attracted to green, orange, red, and yellow light. However, in this case, adult males were more attracted than any other life stage, and white light was the most attractive stimulus [ 36 ], while in our study only 3% of all the insects tested were attracted to this color. Specialist insects tend to detect wavelength related to their host, while generalist insects like L. zonatus respond to a broader wavelength spectrum [ 37 ].…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, nymphs and adults of the Miridae Lygus hesperus Knight were attracted to the green color [ 3 ], and adults of the Pentatomidae Halyomorpha halys were attracted to green, orange, red, and yellow light. However, in this case, adult males were more attracted than any other life stage, and white light was the most attractive stimulus [ 36 ], while in our study only 3% of all the insects tested were attracted to this color. Specialist insects tend to detect wavelength related to their host, while generalist insects like L. zonatus respond to a broader wavelength spectrum [ 37 ].…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, our results support laboratory results in [ 48 ], as it seems that the combination of UV and visible blue light provides higher attraction compared to UV alone. In another experiment, white, yellow, red, orange, and green source lights were attractive to H. halys [ 49 ]. Similarly, in our laboratory experiments, it seems that H. halys can detect and are attracted by either blue, green, or yellow light.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of the trap design consisted of the addition of an electric fan. The light lamp attracted insects to the trap, but they tended to remain close to the light source [ 49 ] and were reluctant to enter inside the funnel bag [Authors personal observation]. The presence of the fan creates a suction vortex that possibly facilitated the movement of the stink bugs to the funnel net cage (similarly to [ 45 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting group of studies have been reported with stink bugs (Hemiptera: Pentatomidae), such as Halyomorpha halys (Stål) and the green stink bugs Nezara spp. (Cambridge et al, 2017; Endo et al, 2022; Rice et al, 2017; Rondoni et al, 2022). Similar studies with several moth species, such as the cabbage looper Trichoplusia ni (Hübner) (Lepidoptera: Noctuidae), the Indian meal moth (IMM), Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), and the tomato leaf miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), have used traps with lights plus sex pheromone/kairomone baits for mass trapping adults (Henneberry et al, 1967; Pezhman & Saeidi, 2018; Sambaraju & Phillips, 2008).…”
Section: Introductionmentioning
confidence: 99%